Introduction: Suicide and suicidal survival - Moi, Ruben (Nordlit, 2024)
«Suicide and suicidal survival», this special issue of Nordlit, examines the presentation of the extremities of the human existence, primarily in literature, but also in popular music, a TV-series, and a graphic novel. Why do some people commit suicide while the vast majority continue their life? What is suicide? And suicidality? Why do literature and art present unique possibilities to reflect upon and to interpret suicide and survival, and an alternative to sociological, philosophical, and psychological approaches to this grave topic? How do we define suicide literature? This introduction and the twelve articles meditate upon such questions, and how these existential inquiries can be apprehended through imaginative sensibility and aesthetic awareness.